Distributed Periodic Event-Triggered Algorithm for Current Sharing and Voltage Regulation in DC Microgrids - Fan, Bo; Peng, Jiangkai; Yang, Qinmin; Liu, Wenxin (IEEE transactions on smart grid, 2020)
In modern control systems, most control algorithms, especially system-level ones, are implemented in discretetime (DT) with digital controllers and digital communications. In this paper, a distributed DT algorithm is developed to achieve proportional load current sharing and average bus voltage regulation in DC microgrids. In order to reduce the communication requirement among the controllers, a periodic event-triggered (PET) DT algorithm is proposed by introducing a novel PET condition. Since the PET condition is detected periodically, the Zeno phenomenon existing in continuous-time (CT) event-triggered algorithms can be avoided. The communication burden for detecting the PET condition is also relieved since only the local and neighbors' triggered information is required. Through the Lyapunov synthesis, the current sharing error is proved to converge to zero asymptotically. Finally, comparative results among different algorithms, based on a detailed switchlevel microgrid model, are given to validate the effectiveness of the proposed PET control design.